Assessment of COVID-19 Incidence and the Ability to Synthesise Anti-SARS-CoV-2 Antibodies of Paediatric Patients with Primary Immunodeficiency - Karolina Pieniawska-Śmiech (MDPI AG, 2021)
Background: Data regarding the course of SARS-CoV-2 infection in children with primary immunodeficiency (PID) is insufficient. The purpose of the study was to evaluate the morbidity and clinical course of COVID-19 and the ability to produce anti-SARS-CoV-2 IgG antibodies in children with PID. Methods: In this retrospective study, medical records of 99 patients aged 0–18 were evaluated. The patients were divided into three groups: PID group (68.69%), control group (19.19%) and patients with ongoing or previous paediatric inflammatory multisystem syndrome (12.12%). Data such as morbidity, clinical outcome, and IgG anti-SARS-CoV-2 antibody titres were assessed. Results: A confirmed diagnosis of SARS-CoV-2 infection has been established in 26.47% of patients with PID. Among patients with PID infected with SARS-CoV-2, only three cases were hospitalised. Mortality in the PID group was 0%. Throughout an observation period of 1 year, 47.06% of patients with PID were tested positive for the anti-SARS-CoV-2 antibody. Conclusions: In the study group, in most cases the disease had a mild and self-limiting course. Remarkably, even though IgG deficiency was the most prevalent form of PID in the study group, the patients were able to respond satisfactorily to the infection in terms of anti-SARS-CoV-2 IgG.